2014
DOI: 10.1097/dbp.0000000000000060
|View full text |Cite
|
Sign up to set email alerts
|

Infants and Toddlers Left Behind

Abstract: Objective To determine (a) how child age relates to parent concerns about child behavior and (b) how child age and parent concerns correlate with provider referrals and family attendance at mental health consultant (MHC) appointments. Methods Data were obtained from Rhode Island’s Project LAUNCH (Linking Actions for Unmet Needs in Children’s Health) in which universal developmental and behavioral screening and MHCs were embedded within primary care sites serving low-income, diverse families. Children 9 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…This care environment provides the longitudinal follow-up of the children, promoting whole health care and contextualizing factors that determine the quality of life and health of the children, in relation to their community. 7 , 8 , 9 As a paradox, many professionals who work in BHC do not feel capable and comfortable to identify and handle possible infant MHPs. 10 The use of standardized screening instruments of MHPs in young children can be a strategy for these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…This care environment provides the longitudinal follow-up of the children, promoting whole health care and contextualizing factors that determine the quality of life and health of the children, in relation to their community. 7 , 8 , 9 As a paradox, many professionals who work in BHC do not feel capable and comfortable to identify and handle possible infant MHPs. 10 The use of standardized screening instruments of MHPs in young children can be a strategy for these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations of models that promote universal behavioral health screening and embed mental health clinicians within primary care sites reveal mixed results (Godoy et al 2014; Spijkers et al 2013; Briggs et al 2012). For example, one model embedding an infant/toddler specialist in primary care settings reported improved ASQ-SE scores (Briggs et al 2012) whereas one offering brief counseling found no improvements over usual care (Spijkers et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one model embedding an infant/toddler specialist in primary care settings reported improved ASQ-SE scores (Briggs et al 2012) whereas one offering brief counseling found no improvements over usual care (Spijkers et al 2013). Results from Project LAUNCH in Rhode Island, an initiative without the family partner role, resulted in improved identification of young children at risk but found that subsequently younger children were less likely than older children to utilize subsequent mental health consultation (Godoy et al 2014). These results highlight needs for innovative family engagement approaches, particularly families with very young children in stressful circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations